Replacing place with space: the influences and the challenges of the new norm on the Milan-Cortina Winter Games 2026 - Raco, M.; Di Vita, S. (Planning Perspectives, 2024)
As part of its ongoing review of the processes surrounding the hosting of the Olympic Games (OGs), the International Olympic Committee (IOC) has set out the Olympic Agenda 2020 and the related New Norm (NN). These reforms, respectively approved in 2014 and 2018 to deal with the growing withdrawal of the bids, are in line with recent management studies highlighting the importance of standardization and replicability in the delivery of physical and social infrastructure. Indeed, they aim to convert development projects, historically-embedded in places, into programmable and transferable spaces of action, in which rules of project management and organization can be applied. The example of the Milano-Cortina Winter Games (MCWG) 2026 is used to assess the first effects and impacts of such IOC`s new approach. At the backdrop of the historical evolution of mega event planning in post-war Italy, the rolling-out of the MCWG is examined at the multiple scales of the Olympic macro-region and of the Milan Olympic Village. The analysis shows that, despite the objectives of the NN to overcome existing tensions and conflicts in the involved places, the Games has only succeeded in amplifying them. Such contradiction demands for a further reflection on this model, that remains under-discussed and under researched